2008
DOI: 10.1080/13550280802216502
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal apoptosis does not play an important role in human rabies encephalitis

Abstract: It is generally accepted that there are not prominent features of neuronal cell death in rabies encephalitis. However, Hemachudha and coworkers recently reported widespread apoptosis in the central nervous system of several human rabies cases (BMC Infect Dis 5: 104, 2005). In this study we have evaluated morphological features and markers of neuronal apoptosis in postmortem brain tissue from 12 cases of human rabies who died in four different countries. Histopathological analysis, TUNEL (terminal deoxynucleoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
39
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 22 publications
8
39
1
3
Order By: Relevance
“…En general, la apoptosis no parece ser un fenómeno importante en la fisiopatología de la rabia (30,31). Sin embargo, es posible que el virus genere alteraciones funcionales en las neuronas que expresan esta proteína.…”
Section: Efecto De La Infección Viral Sobre La Expresión De Cb Y Pvunclassified
“…En general, la apoptosis no parece ser un fenómeno importante en la fisiopatología de la rabia (30,31). Sin embargo, es posible que el virus genere alteraciones funcionales en las neuronas que expresan esta proteína.…”
Section: Efecto De La Infección Viral Sobre La Expresión De Cb Y Pvunclassified
“…42,45 Contrary to previous reports, 46 we have recently provided strong evidence that neuronal apoptosis does not play an important role in human rabies. 47 Hence, in rabies virus infection there are complex mechanisms involved in the death or survival of neurons both in vitro and in animal models using different viral strains and routes of inoculation, but neuronal cell death is not prominent in natural rabies. Neuronal apoptosis is a host mechanism employed to limit viral spread and does not serve a fundamental role in the pathogenesis of rabies.…”
Section: Mechanisms For Neuronal Dysfunction and Deathmentioning
confidence: 99%
“…Street-virusinfected suckling mice revealed TUNEL labelling of occasional microglial cells in the cerebral cortex and brain stem (21). On the other hand, evaluation of morphological features of neuronal apoptosis in postmortem brain tissue from human rabies victims collected from different countries suggested that neuronal apoptosis does not play an important role in human rabies encephalitis (11).…”
Section: Discussionmentioning
confidence: 99%